Molecular sieve catalyst for purifying and recycling CO in soot and preparation method of molecular sieve catalyst

By using molecular sieve catalysts made of zeolite powder, phthalidite, copper-based composition and calcium-based composition, the technical difficulties of CO purification and recovery in industrial coal soot are solved, and efficient and economical CO adsorption and purification effects are achieved.

CN119588306AInactive Publication Date: 2025-03-11XUYI OASIS IND TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411901311.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as the catalyst support being prone to spontaneous ignition, poor adsorption effect on low-concentration CO, and prone to inactivity in the purification and recovery of CO in industrial coal soot.

Method used

The molecular sieve catalyst made of zeolite powder, zeolite, copper-based composition and calcium-based composition are used to improve the catalyst's resistance to high temperature, corrosion, acid resistance and pressure resistance through specific preparation methods.

Benefits of technology

It realizes efficient adsorption and purification and recovery of low concentrations of carbon monoxide, and the catalyst has good regeneration ability and long life, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588306A_ABST
    Figure CN119588306A_ABST
Patent Text Reader

Abstract

The invention provides a molecular sieve catalyst for purifying and recycling CO in soot. The molecular sieve catalyst is mainly prepared from the following raw materials in parts by weight: 65-70 parts of zeolite powder; 30 to 35 parts of pseudo-boehmite; 7.5 to 8.5 parts of a copper-based composition; and 9.2 to 12.5 parts of a calcium-based composition. The Cax type zeolite powder, the Nax type zeolite powder and the pseudo-boehmite are used as catalyst carrier raw materials, and the adsorption capacity and the adsorption selectivity of carbon monoxide are greatly improved through cooperation of the Cax type zeolite powder, the Nax type zeolite powder and the pseudo-boehmite, so that the final molecular sieve can achieve the effects of high temperature resistance, corrosion resistance, acid resistance and pressure resistance; the molecular sieve catalyst has good adsorptive selectivity on low-concentration carbon monoxide, and is suitable for purification and recovery of carbon monoxide in industrial soot.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieve catalysts for purifying and recovering CO, and in particular to a molecular sieve catalyst for purifying and recovering CO in coal smoke and a preparation method thereof. Background Art

[0002] In the context of global response to climate change, the country has taken positive actions and promulgated a series of policies and regulations such as the "Interim Regulations on Carbon Emission Trading Management". The core purpose is to comprehensively regulate and vigorously promote energy conservation and carbon reduction. Among them, strengthening carbon emission intensity management is one of the key tasks. To this end, the country has implemented precise policies based on the characteristics of different fields and industries and vigorously promoted special actions for energy conservation and carbon reduction. The coal smoke impurity treatment strategy, as an important part of the overall environmental protection and climate change response strategy, has been formally incorporated into the relevant decision-making system, which fully demonstrates its key position in environmental protection work.

[0003] Soot is the smoke emitted during the combustion of coal. There are many impurities in soot, including water vapor, sulfur dioxide, nitrogen, hydrogen, oxygen, carbon monoxide CO, carbon dioxide CO2, hydrocarbons and dozens of other impurities. It is widely present in many industries, such as blast furnaces, coke ovens, boilers, power plants, and coal chemical industries. The soot produced by these industries accounts for a considerable proportion of the entire environmental protection industry, exceeding 35%. Due to the wide variety of coal types used in various industries, the combustion conditions are also very different, and the purification measures taken are different, resulting in obvious diversity and differences in the impurity components of coal-based flue gas in different industries. The treatment of soot impurities faces many challenges, and one of the key factors is the selection of catalysts.

[0004] For the application of industrial soot purification, activated carbon is generally selected as the traditional catalyst carrier. However, due to the high temperature of industrial soot, activated carbon as a catalyst carrier is prone to spontaneous combustion under high temperature conditions, and the activated carbon has a poor adsorption effect on low-concentration carbon monoxide. There are also some toxic, acidic, oxidizing substances and dust impurities in soot. If the catalyst adsorption and desorption material is not selected correctly, it is likely to cause the catalyst to lose its activity. Therefore, the material selection for preparing the catalyst is particularly important. Summary of the invention

[0005] The present invention aims to at least partially overcome the above-mentioned technical problems and / or other potential problems existing in the prior art: to provide a molecular sieve catalyst for purifying and recovering CO in coal smoke and a preparation method thereof. The molecular sieve catalyst has good adsorption selectivity for low-concentration carbon monoxide, and is resistant to high temperature, corrosion, acid and pressure, and is suitable for purifying and recovering carbon monoxide in industrial coal smoke.

[0006] The technical solution of the present invention is as follows: The present invention first provides a molecular sieve catalyst for purifying and recovering CO in coal smoke, which is mainly made of the following raw materials in parts by weight: 65-70 parts of zeolite powder; 30-35 parts of pseudo-boehmite; 7.5-8.5 parts of copper-based composition; and 9.2-12.5 parts of calcium-based composition.

[0007] Preferably, the zeolite powder is one or a mixture of Cax-type and Nax-type zeolite powders.

[0008] Preferably, the copper-based composition is one or a mixture of copper oxide, copper chloride, copper sulfide, cuprous oxide, cuprous sulfide, cuprous chloride, and copper nitrate.

[0009] Preferably, the calcium-based composition is a mixture of one or more of calcium oxide, calcium chloride, calcium sulfide, calcium carbonate, calcium nitrate and calcium hydroxide.

[0010] The present invention provides a method for preparing a molecular sieve catalyst for purifying and recovering CO in coal smoke, comprising the following steps: 1) First, zeolite powder and pseudo-boehmite are mixed and ground to a fineness of 325-500 mesh, and then granulated. After granulation, the granules are dried at 120-180° C. until the moisture content of the granules is less than 10wt%, and then calcined at 575-630° C. for 2-3 hours, and cooled to obtain a catalyst carrier; 2) Add the copper-based composition into water, disperse it evenly, heat it to 90-100°C and keep it at a constant temperature for 4-6 hours, cool it to room temperature to obtain a copper-based impregnation solution, add the catalyst carrier prepared in step 1) into the copper-based impregnation solution for immersion exchange for 8-12 hours, then take it out and dry it, place it at 300-350°C for high temperature regeneration for 5-6 hours to complete the copper-based loading; 3) Add the calcium-based composition into water and disperse it evenly, then heat it to 90-100°C and keep it at a constant temperature for 4-6 hours, and cool it to room temperature to obtain a calcium-based impregnation solution. Add the copper-based catalyst carrier completed in step 2) into the calcium-based impregnation solution for immersion exchange for 8-12 hours, then take it out and dry it, and place it at 300-350°C for high temperature regeneration for 5-6 hours to obtain a molecular sieve catalyst.

[0011] Preferably, the granulation may be spray spheronization or extrusion granulation.

[0012] The present invention provides another method for preparing a molecular sieve catalyst for purifying and recovering CO in coal smoke, comprising the following steps: 1) Mix zeolite powder and pseudo-boehmite and grind them to a fineness of 325-500 mesh, then put them into a kneader, first knead the dry powder for 30-40 minutes, then add the copper-based composition, calcium-based composition and 30-42% water by weight of the solid material, knead for 30-40 minutes, then add 10-15% silica sol by weight of the solid material, and knead again for 30-40 minutes to obtain a high-viscosity mud; 2) The high viscosity mud prepared in step 1) is aged for 46-72 hours, then put into an extruder to extrude columnar particles, the particles are surface dried for 23-48 hours, dried at 120-180° C. until the moisture content of the particles is less than 10wt%, and then calcined at 575-600° C. for 2-3 hours, and cooled to obtain a molecular sieve catalyst.

[0013] As an optimization, the SiO2 content in the silica sol is 20-30wt%; The beneficial effects of the present invention are as follows: the present invention uses Cax type, Nax type zeolite powder and pseudo-boehmite as catalyst carrier raw materials, and their combination greatly improves the adsorption amount and adsorption selectivity of carbon monoxide, so that the final molecular sieve can achieve the effects of high temperature resistance, corrosion resistance, acid resistance and pressure resistance; Cax type and Nax type zeolite powder have high specific surface area and uniform pore size distribution, and can efficiently and selectively adsorb and separate carbon monoxide. Pseudo-boehmite, as an incompletely crystallized aluminum oxide hydrate, has the characteristics of large pore volume and high specific surface area. Pseudo-boehmite is widely used as a catalyst carrier in the petrochemical industry as catalytic cracking, catalytic hydrogenation, aromatic cracking and environmental protection chemical industry. Pseudo-boehmite with large pore volume and high specific surface area is one of the multi-purpose catalyst carrier materials. Pseudo-boehmite not only has good corrosion resistance, but also can be used as a binder for catalysts. Pseudo-boehmite has a unique structure and can bind metal atoms to its surface layer, which can reduce reaction time, reduce energy consumption and improve reaction efficiency. The performance of pseudo-boehmite in the adsorption of CO, such as when the temperature is constant at about 50°C and the pressure is less than 1MPa, its maximum CO adsorption can reach 11%, and the water absorption rate can be as high as 40% or more. The molecular sieve catalyst of the present invention can be regenerated repeatedly, and the service life is greater than 5 years. It can also be activated at high temperature, and the adsorbed material of the carrier after activation is removed, and the appearance color is restored. Compared with the high price of the precious metal catalyst in the prior art, it brings the disadvantage of high production cost to users. The present invention uses a copper-based composition combined with a calcium-based composition to achieve a bimetallic element catalyst with good catalytic activity, high selectivity and stable reaction temperature, greatly reducing the product price. The role of the copper-based composition not only increases the operating temperature of the catalyst, but also improves the absorption effect of the catalyst on low-concentration CO. The copper-based composition has excellent characteristics in the catalyst, which promotes the adsorption and activation performance of CO on the copper base. The role of the calcium-based composition is to improve the catalytic activity of the catalyst, accelerate the reaction rate, and at the same time have high selectivity and reaction temperature stability, so that the soot finally meets the environmental emission standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a physical morphology diagram of the molecular sieve catalyst prepared in Example 5.

[0015] Figure 2 This is a physical morphology diagram of the molecular sieve catalyst prepared in Example 6. DETAILED DESCRIPTION

[0016] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0017] Example 1 1) 40kg of Cax zeolite, 30kg of Nax zeolite and 30kg of pseudo-boehmite are mixed and ground to a fineness of 325-500 mesh, and then put into a kneading machine. First, the dry powder is kneaded for 30 minutes, and then 36% of the weight of water is added. After kneading for 30 minutes, 10% of the weight of silica sol is added, and the SiO2 content in the silica sol is 20wt%; knead again for 40 minutes to obtain a high-viscosity mud; the above kneaded high-viscosity mud has become a high-viscosity mud, and the mud is unloaded into a stainless steel rectangular storage device, and then the storage device is completely covered with a damp cotton cloth to ensure the moisture of the mud. This method is to age the clay material of the catalyst carrier. Aging the clay material reduces the pH value in the clay material, improves the formation of colloidal substances in the clay material, increases plasticity, develops patina, increases strength, prevents cracking, and reduces powder loss. The aged silica sol can provide a larger catalytic reaction area for the catalyst when preparing the catalyst carrier. The aging time is 46-48 hours in summer and autumn, and 60-72 hours in winter and spring. The aged clay material is then placed in an extruder for extrusion into columnar particles with a diameter of 5.1-5.3mm and a length of 4-18mm. The prepared columnar particles are dried for 24 hours in summer and autumn, and 48 hours in winter and spring. The columnar particles with dried surfaces are then placed in a belt furnace at 120-180°C for 2-3 hours for drying. After the moisture is reduced to less than 10%, they are passed through a high-temperature rotary kiln at 630°C for 3 hours and then cooled to form a catalyst carrier. 2) 8.5 kg of a mixture of copper oxide and cuprous chloride in equal weight ratio was added to 10 kg of water, dispersed evenly, and then heated to 90° C. for 6 hours, cooled to room temperature to obtain a copper-based impregnation solution, and the catalyst carrier prepared in step 1) was added to the copper-based impregnation solution for immersion exchange for 12 hours, then taken out and dried, and placed at 350° C. for high-temperature regeneration for 6 hours to complete the copper-based loading; 3) 9.2 kg of a mixture of calcium oxide and calcium carbonate in an equal weight ratio was added to 10 kg of water, dispersed evenly, and heated to 90° C. for 6 hours, cooled to room temperature to obtain a calcium-based impregnation solution, and the copper-based catalyst carrier completed in step 2) was added to the calcium-based impregnation solution for immersion exchange for 12 hours, then taken out and dried, and placed at 350° C. for high-temperature regeneration for 6 hours to obtain a molecular sieve catalyst.

[0018] The test indicators of the obtained molecular sieve catalyst are as follows: Catalyst appearance: yellow or grayish yellow (columnar); Specification diameter: 5.1-5.3mm (length 4-18mm); Crushing strength: 90-150 N / particle; Static water adsorption: 27.0-28.5wt%; Specific surface area: 600-720m 2 / g; porosity: 65-75%; CO adsorption: 15-17.5 wt%; CO2 adsorption: 6-9wt%; NOx adsorption: 10-14.5wt%; mercury desorption rate: 0.03%; denitrification rate: 0.02%; sulfur dioxide desorption rate: 0.01%.

[0019] Example 2 The preparation method of the catalyst carrier in this embodiment is the same as step 1) of embodiment 1. The difference is that step 2) and step 3) are as follows: 2) Add 8.5 kg of copper chloride to 10 kg of water, disperse evenly, heat to 90° C. and keep constant temperature for 6 hours, cool to room temperature to obtain a copper-based impregnation solution, add the catalyst carrier prepared in step 1) to the copper-based impregnation solution and impregnate for 8 hours, then take out and dry, place at 350° C. for high temperature regeneration for 5 hours to complete the copper-based loading; 3) Add 9.2 kg of calcium chloride to 10 kg of water, disperse evenly, heat to 90 ° C and keep constant temperature for 6 hours, cool to room temperature to obtain a calcium-based impregnation solution, add the copper-based catalyst carrier completed in step 2) to the calcium-based impregnation solution for immersion exchange for 8 hours, then take out and dry, and place it at 350 ° C for high temperature regeneration for 6 hours to obtain a molecular sieve catalyst.

[0020] The test indicators of the obtained molecular sieve catalyst are as follows: Catalyst appearance: yellow or grayish yellow (columnar); Specification diameter: 5.1-5.3mm (length 4-18mm); Compressive strength: 100-150N / particle; Static water adsorption: 27.0-28.0wt%; Specific surface area: 600-700 m 2 / g; porosity: 65-73%; CO adsorption: 15-17wt%; CO2 adsorption: 6-8.75 wt%; NOx adsorption: 10-14.0wt%; mercury desorption rate: 0.02%; nitrate desorption rate: 0.01%; sulfur dioxide desorption rate: 0.01%.

[0021] Example 3 1) 40kg of Cax zeolite, 30kg of Nax zeolite and 30kg of pseudo-boehmite are mixed and ground to a fineness of 325-500 mesh and then put into a kneader. First, the dry powder is kneaded for 30 minutes, and then 8.5kg of a copper-based composition (a mixture of copper nitrate Cu(NO3)2 and cuprous oxide Cu2O in equal weight ratio), 9.2kg of a calcium-based composition (calcium sulfide CaS and calcium hydroxide Ca(OH)2 in equal weight ratio) and 36% of water by weight of the solid material are added. After kneading for 40 minutes, 10% of the weight of the solid material of silica sol is added, and kneading is performed again for 40 minutes to obtain a high-viscosity mud; the SiO2 content in the silica sol is 20wt%; 2) The high-viscosity clay prepared in step 1) is aged for 46 hours, the main purpose of which is to reduce the pH value in the clay, improve the colloidal substances of the clay, increase the dispersion of raw materials and metal elements, and increase the specific surface area of ​​the catalyst. Then the aged clay is taken out and put into the extruder to extrude catalyst particles with a columnar diameter of 5.1-5.3mm and a column length of 4-18mm. The surface of the columnar catalyst particles is dried for 48 hours, and then dried in a belt dryer at 120-180℃ for 2-3 hours. After drying until the moisture content of the catalyst particles is less than 10%, it is then roasted at 600℃ for 3 hours and cooled to obtain a molecular sieve catalyst.

[0022] The test indicators of the obtained molecular sieve catalyst are as follows: Catalyst appearance: beige or grayish yellow (columnar); Specification diameter: 5.1-5.3mm (length 4-18mm); Compressive strength: 100-150N / particle; Static water adsorption: 26.5-26.9wt%; Specific surface area: 600-690 m 2 / g; porosity: 65-70%; CO adsorption: 14-16wt%; CO2 adsorption: 6-6.5 wt%; NOx adsorption: 7-9.0wt%; mercury desorption rate: 0.1%; nitrate desorption rate: 0.2%; sulfur dioxide desorption rate: 0.02%.

[0023] Example 4 1) 40kg of Cax zeolite, 30kg of Nax zeolite and 30kg of pseudo-boehmite are mixed and ground to a fineness of 325-500 mesh and then put into a kneader. First, the dry powder is kneaded for 30 minutes, and then 8.5kg of a copper-based composition (a mixture of copper sulfide CuS and copper chloride CuCl2 in an equal weight ratio), 9.2kg of a calcium-based composition (a mixture of calcium chloride and calcium carbonate in an equal weight ratio) and 36% of water by weight of the solid material are added. After kneading for 40 minutes, 13% of the weight of the solid material of silica sol is added, and kneading is performed again for 40 minutes to obtain a high-viscosity mud; the SiO2 content in the silica sol is 20wt%; 2) The high-viscosity clay prepared in step 1) is aged for 46 hours, the main purpose of which is to reduce the pH value in the clay, improve the colloidal substances of the clay, increase the dispersion of raw materials and metal elements, and increase the specific surface area of ​​the catalyst. Then the aged clay is taken out and put into the extruder to extrude catalyst particles with a columnar diameter of 5.1-5.3mm and a column length of 4-18mm. The surface of the columnar catalyst particles is dried for 48 hours, and then dried in a belt dryer at 120-180℃ for 2-3 hours. After drying until the moisture content of the catalyst particles is less than 10%, it is then roasted at 600℃ for 3 hours and cooled to obtain a molecular sieve catalyst.

[0024] The test indicators of the obtained molecular sieve catalyst are as follows: Catalyst appearance: beige or grayish yellow (columnar); Specification diameter: 5.1-5.3mm (length 4-18mm); Compressive strength: 100-150N / particle; Static water adsorption: 26.5-27wt%; Specific surface area: 600-690 m 2 / g; porosity: 65-73%; CO adsorption: 13-14.5wt%; CO2 adsorption: 6-6.2 wt%; NOx adsorption: 6-8.0wt%; mercury desorption rate: 0.5%; nitrate desorption rate: 0.2%; sulfur dioxide desorption rate: 0.01%.

[0025] Example 5 1) 70kg of Cax zeolite and 30kg of pseudo-boehmite are mixed and ground to a fineness of 325-500 mesh, and then put into a kneader, firstly, the dry powder is kneaded for 30 minutes, then 7.5kg of a mixture of copper sulfide and copper nitrate in an equal weight ratio, 12.5kg of a mixture of calcium chloride and calcium sulfide in an equal weight ratio, and 36% of water by weight of the solid material are added, and after kneading for 40 minutes, 13% of the weight of the solid material of silica sol is added, and kneading is performed again for 40 minutes to obtain a high-viscosity mud; the SiO2 content in the silica sol is 20wt%; 2) The high-viscosity clay prepared in step 1) is aged for 46 hours. The main purpose is to reduce the pH value in the clay, improve the colloidal substances in the clay, increase the dispersion of raw materials and metal elements, and increase the specific surface area of ​​the catalyst. Then the aged clay is taken out and put into the extruder to extrude catalyst particles with a columnar diameter of 5.1-5.3mm and a column length of 4-18mm. The surface of the columnar catalyst particles is dried for 48 hours, and then dried in a belt dryer at 120-180℃ for 2-3 hours. After drying until the moisture content of the catalyst particles is less than 10%, it is then calcined at 600℃ for 3 hours and cooled to obtain a molecular sieve catalyst. The actual form is as follows: Figure 1 shown.

[0026] The test indicators of the obtained molecular sieve catalyst are as follows: Catalyst appearance: beige or grayish yellow (columnar); Specification diameter: 5.1-5.3mm (length 4-18mm); Compressive strength: 120-160N / particle; Static water adsorption: 28.0-29.2wt%; Specific surface area: 600-700 m 2 / g; porosity: 66-76%; CO adsorption: 16.2-18.5wt%; CO2 adsorption: 7-11 wt%; NOx adsorption: 15-16.0wt%; mercury desorption rate: 0.6%; nitrate desorption rate: 0.3%; sulfur dioxide desorption rate: 0.04%.

[0027] Example 6 1) 70 kg of Cax zeolite and 30 kg of pseudo-boehmite were mixed and ground to a fineness of 325-500 mesh, and then put into a granulator for pelletizing. After granulation, the diameter of the spherical particles was 5-7 mm. The spherical particles were dried for 48 hours and then put into a belt furnace at 120-180° C. for 2-3 hours until the moisture content was less than 10wt%, and then calcined at 630° C. for 2-3 hours, and cooled to obtain a catalyst carrier; 2) Add 7.5 kg of a mixture of copper nitrate and copper sulfide in equal weight ratio into 10 kg of water, disperse evenly, heat to 90-100° C. and keep constant temperature for 4-6 hours, cool to room temperature to obtain a copper-based impregnation solution, add the catalyst carrier prepared in step 1) into the copper-based impregnation solution for impregnation exchange for 8-12 hours, then take out and dry, place at 350° C. for high temperature regeneration for 5-6 hours to complete the copper-based loading; 3) Add 12.5 kg of a mixture of calcium sulfide and calcium chloride in equal weight ratio into 10 kg of water, disperse evenly, heat to 90-100°C and keep constant for 4-6 hours, cool to room temperature to obtain a calcium-based impregnation solution, add the copper-based catalyst carrier completed in step 2) into the calcium-based impregnation solution for 8-12 hours, then take out and dry, place at 350°C for high temperature regeneration for 5-6 hours, and obtain a molecular sieve catalyst. The physical form is as follows: Figure 2 shown.

[0028] The test indicators of the obtained molecular sieve catalyst are as follows: Catalyst appearance: yellow or grayish yellow (spherical); Specification diameter: 5-7mm; Crushing strength: 140-200 N / particle; Static water adsorption: 28.0-29.0wt%; Specific surface area: 600-700m 2 / g; porosity: 66-76%; CO adsorption: 16-18.2 wt%; CO2 adsorption: 7.0-11.0wt%; NOx adsorption: 15-16wt%; mercury desorption rate: 0.65%; denitrification rate: 0.3%; sulfur dioxide desorption rate: 0.05%.

[0029] It can be seen from the detection parameters of the above embodiments that embodiments 5-6 are the better solutions of the present invention.

[0030] The above are only examples of the characteristic implementation of the present invention, and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent exchange or equivalent replacement shall fall within the protection scope of the present invention.

Claims

1. A molecular sieve catalyst for purifying and recovering CO in coal smoke, characterized in that: The invention is mainly prepared from the following raw materials in parts by weight: 65-70 parts of zeolite powder; 30-35 parts of pseudo-boehmite; 7.5-8.5 parts of copper-based composition; and 9.2-12.5 parts of calcium-based composition.

2. The molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 1, characterized in that: The zeolite powder is one of Cax type and Nax type zeolite powder or a mixture of both.

3. The molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 2, characterized in that: The copper-based composition is one or a mixture of copper oxide, copper chloride, copper sulfide, cuprous oxide, cuprous sulfide, cuprous chloride and copper nitrate.

4. The molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 3, characterized in that: The calcium-based composition is a mixture of one or more of calcium oxide, calcium chloride, calcium sulfide, calcium carbonate, calcium nitrate and calcium hydroxide.

5. A method for preparing a molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 1, characterized in that: The following steps are involved: 1) First, zeolite powder and pseudo-boehmite are mixed and ground to a fineness of 325-500 mesh, and then granulated. After granulation, the granules are dried at 120-180° C. until the moisture content of the granules is less than 10wt%, and then calcined at 575-630° C. for 2-3 hours, and cooled to obtain a catalyst carrier; 2) Add the copper-based composition into water, disperse it evenly, heat it to 90-100°C and keep it at a constant temperature for 4-6 hours, cool it to room temperature to obtain a copper-based impregnation solution, add the catalyst carrier prepared in step 1) into the copper-based impregnation solution for immersion exchange for 8-12 hours, then take it out and dry it, place it at 300-350°C for high temperature regeneration for 5-6 hours to complete the copper-based loading; 3) Add the calcium-based composition into water and disperse it evenly, then heat it to 90-100°C and keep it at a constant temperature for 4-6 hours, and cool it to room temperature to obtain a calcium-based impregnation solution. Add the copper-based catalyst carrier completed in step 2) into the calcium-based impregnation solution for immersion exchange for 8-12 hours, then take it out and dry it, and place it at 300-350°C for high temperature regeneration for 5-6 hours to obtain a molecular sieve catalyst.

6. The method for preparing a molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 5, characterized in that: The granulation can be spray spheronization or extrusion granulation.

7. A method for preparing a molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 1, characterized in that: The following steps are involved: 1) Mix zeolite powder and pseudo-boehmite and grind them to a fineness of 325-500 mesh, then put them into a kneader, first knead the dry powder for 30-40 minutes, then add the copper-based composition, calcium-based composition and 30-42% water by weight of the solid material, knead for 30-40 minutes, then add 10-15% silica sol by weight of the solid material, and knead again for 30-40 minutes to obtain a high-viscosity mud; 2) The high viscosity mud prepared in step 1) is aged for 46-72 hours, then put into an extruder to extrude columnar particles, the particles are surface dried for 23-48 hours, dried at 120-180° C. until the moisture content of the particles is less than 10wt%, and then calcined at 575-600° C. for 2-3 hours, and cooled to obtain a molecular sieve catalyst.

8. The method for preparing a molecular sieve catalyst for purifying and recovering CO in coal smoke according to claim 7, characterized in that: The SiO2 content in the silica sol is 20-30wt%.

Citation Information

Patent Citations

  • High-efficiency CO adsorbent and preparation method thereof

    CN110270303A

  • Preparation method and application method of monovalent-copper-loaded molecular sieve adsorbent

    CN112844305A

  • Modified calcium low-silicon zeolite molecular sieve and preparation method thereof

    CN113371730A